Disabled independent living : from the perspectives of built environment / Nurul Fadzila Zahari ... [et al.] - Zahari, Nurul Fadzila; Che Ani, Adi Irfan; Abdul Rashid, Robiah; Hashim, Haslina; Taharuddin, Nurul Shima (Universiti Teknologi MARA, Perak, 2020)
In 2006, Malaysia has signed the Convention of Rights of Person with Disabilities (CRPD) and put oath to promote, protect and ensure the full and equal enjoyment of all human rights and fundamental freedoms by all persons with disabilities. Even with the advent of the UNCRPD, the existing built environment fails the neighbourhood accessibility needs of people with disability. Little is known about the extent of built environment inaccessibility, and an improved measure, at a neighbourhood scale, is required. This paper argues that built environment practitioners must recognize the disabling potency of current built environment practice. It argues that they need to engage directly with people with disabilities to improve understanding of accessibility needs.